The indusium griseum and the longitudinal striae of the corpus callosum. (January 2015) - Di Ieva, Antonio; Fathalla, Hussein; Cusimano, Michael D.; Tschabitscher, Manfred
Abstract: In the eighteenth century, Lancisi described the indusium griseum (IG) and the longitudinal striae (LS) of the corpus callosum. The IG is a thin neuronal lamina above the corpus callosum, covered on each side of the midline by the medial and lateral LS. The medial LS (nerves of Lancisi) and lateral LS are two pairs of myelinated fiber bands found in the gray matter of the IG on the dorsal aspect of the corpus callosum. Embryologically, the IG and LS are dorsal remnants of the archicortex of the hippocampus and fornix and thus they are considered components of the limbic system. Recent studies using immunohistochemistry reported that acetylcholine, dopamine, noradrenaline, 5-hydroxytryptamine and GABA neurons innervate the IG. Newer imaging techniques, such as high field MRI and diffusion tensor imaging, provide new tools for studying these structures, whose true function remains still unclear. The present paper reviews the history of the discovery of the IG and LS of the corpus callosum, with a holistic overview on these interesting structures from the anatomical, embryological, neurochemical, radiological and clinical perspective.